(untitled) - DE LA TORRE, FRANCISCO (Mexico, 1992)
1.Motivation / 2.At the travel agency / 3.Traveling documents / 4.Atourist guide / 5.Getting ready for the trip / 6.At the airport / 7.On board the plane / 8.Immigration / 9.Review lesson / 10.Health control / 11.Custom house / 12.Reception at the hotel / 13.Registering at the hotel / 14.Changing money / 15.At the restaurant / 16.Placing a telephone call / 17.Sightseeing tours / 18.Revio lesson
Keywords: INGLES - TURISMO